Kaempferol Interferes with Varicella-Zoster Virus Replication in Human Foreskin Fibroblasts - Subin Park; Na-Eun Kim; Bang Ju Park; Hak Cheol Kwon; Yoon-Jae Song (MDPI AG, 2022)
Kaempferol, a natural flavonoid abundantly found in plants, is known to have pharmacological properties, such as anti-inflammatory and anti-cancer effects. In this study, we investigated the antiviral effects of kaempferol against a varicella-zoster virus (VZV) clinical isolate in vitro. We found that kaempferol significantly inhibited VZV replication without exhibiting cytotoxicity. Kaempferol exerted its antiviral effect at a similar stage of the VZV life cycle as acyclovir, which inhibits VZV DNA replication. Taken together, our results suggest that kaempferol inhibits VZV infection by blocking the DNA replication stage in the viral life cycle.